Metastasis-inducing S100A4 protein is associated with the disease activity of rheumatoid arthritis - Oslejsková, Lucie; Grigorian, Mariam; Hulejová, Hana; Vencovsky, Jirí; Pavelka, Karel; Klingelhöfer, Jörg; Gay, Steffen; Neidhart, Michel; Brabcová, Hana; Suchy, David; Senolt, Ladislav (Rheumatology (Oxford, England), 2009)
OBJECTIVES: To evaluate the association between metastasis-inducing protein S100A4 and disease activity in patients with RA, and to demonstrate the effect of TNF-alpha blocking therapy on plasma levels of S100A4 in these patients. METHODS: Plasma levels of the S100A4 protein were analysed in 40 anti-TNF-alpha naive patients with active RA. Of the 40 patients, 25 were treated with adalimumab and monitored over time. The conformational form of S100A4 was analysed using size-exclusion gel chromatography. TNF-alpha mRNA expression and protein synthesis were analysed by RT-PCR and ELISA, respectively. RESULTS: Baseline levels of S100A4 were significantly correlated with disease activity in RA patients (r = 0.41; P < 0.01). After 12 weeks of treatment with adalimumab, there was an obvious shift in the conformations of S100A4 from the multimeric to the dimeric forms, whereas the total levels of the S100A4 protein remained unchanged. This suggests that the bioactive (multimer) S100A4 may decline in response to successful treatment with adalimumab. In addition, we showed significant up-regulation of TNF-alpha mRNA (P < 0.01), and protein release to the cell culture medium of monocytes stimulated with the S100A4 multimer compared with those treated with the dimer and to the unstimulated monocytes (P < 0.001). CONCLUSIONS: This is the first study to show that the levels of the S100A4 protein are correlated with RA disease activity. Furthermore, only the bioactive form, but not the total amount of S100A4, decreases after successful TNF-alpha blocking therapy in patients with RA. These data support an important role for the S100A4 multimer in the pathogenesis of RA.
Keywords: RNA, Messenger; Male; monoklonální protilátky; biologické markery; Up-Regulation; S100 Calcium-Binding Protein A4; Tumor Necrosis Factor-alpha; Biomarkers; monocyty; S100 kalcium vázající protein A4; proteiny S100; adalimumab; Adult; Adalimumab; upregulace; dospělí; mužské pohlaví; lidé středního věku; polymerázová řetězová reakce s reverzní transkripcí; Severity of Illness Index; humanizované monoklonální protilátky; Antibodies, Monoclonal, Humanized; S100 Proteins; kultivované buňky; revmatoidní artritida; Arthritis, Rheumatoid; lidé; ženské pohlaví; Humans; Monocytes; Antirheumatic Agents; antirevmatika; Reverse Transcriptase Polymerase Chain Reaction; TNF-alfa; Cells, Cultured; Antibodies, Monoclonal; stupeň závažnosti nemoci; Female; messenger RNA; Middle Aged